I-2-mediated regioselective C-3 azidation of indoles - Prasad, Pragati K.; Kalshetti, Rupali G.; Reddi, Rambabu N.; Kamble, Sanjay P.; Sudalai, Arumugam (Organic & Biomolecular Chemistry, 2016)
An unprecedented synthesis of novel 3-azido indoles has been developed using I-2 and NaN3 in high yields and excellent regio-selectivity. The reaction proceeds under metal-free conditions at room temperature. Essentially, an umpolung in reactivity at the C-3 position of indole has been achieved by the activation of indoles with I-2.